Spanish menstrual literacy and experiences of menstruation - Sara Sánchez López; Dani Jennifer Barrington; Rocio Poveda Bautista; Santiago Moll López (BMC, 2023)
Abstract There is growing recognition of the important role menstrual health plays in achieving health, education, and gender equity. Yet, stigmatisation and taboo remain present and negative emotions like fear and shame dominate the narrative when speaking about periods. This paper analyses how formal and informal menstrual education is received in Spain, to understand the role of menstrual health literacy in the way menstruation is experienced, and to identify what information would be useful to integrate into formal menstrual education. An online survey with more than 4000 participants (aged between 14 and 80, both people who will/do/have previously menstruate/d and those who do not menstruate) was conducted. Data was gathered using the digital platform Typeform, descriptive and inferential statistical analyses were performed with SPSS software and qualitative data was thematically analysed using Nvivo. Many participants declared not having received sufficient information on menstruation prior to menarche, particularly about how to physically manage it. Furthermore, negative emotions like shame, worry, and fear were recurrently reported to describe menarche; this has not changed between generations. Interestingly, we saw an increase in stress and sadness with an increase in perceived knowledge of the reproductive role of menstruation. We did observe a reduction in negative emotions when people who menstruate perceived they had sufficient information on how to manage their first bleeding. It is recommended that menstrual education beyond reproductive biology, particularly including how to physically manage periods, is integrated into school curricula. Menstrual education of everyone - including those who do not menstruate-can improve how periods are experienced in Spain.